Online Vs Onsite: Dilema Orang Kristen dalam Beribadah di Zaman Teknologi (International Forum of Researchers and Lecturers, 2024)
Communication technology is experiencing rapid development. The internet and digital devices are the result of technological developments. With the internet and digital devices, it is possible to carry out various activities, for example pastoral activities such as online fellowhsip. Online fellowship is increasingly developing following technological advances. Online fellowship began to be widely carried out during the COVID-19 pandemic. The aim of this research is to find out more about online fellowship, its comparison with on-site fellowship and the opinions of Christians regarding online fellowship. The results of this research can be used to answer the dilemma of Christians who practice online fellowship.